Transcription in Rare Books Cataloging. Issue 5 (17th August 2016) - Sjökvist, Peter
ABSTRACT: The implementation of RDA poses questions regarding its application on early printed material, e.g., concerning transcription of title information. Cataloging rules used today for early printed books often include a normalization that is misleading, both for libraries and for users. In this article, ideas concerning transcription according to RDA are discussed. These ideas focus on the double purposes of identifying and retrieving an item. For the first purpose, I suggest a transcription of the title, which closely follows the original ("take what you see"), and for the second, a completely normalized variant title.